2023
DOI: 10.3390/ma16093557
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Strength of Consolidated Powder Materials with a Pull-Based Tester

Abstract: In recent years, there has been increasing interest in the agglomeration of bulk materials. New methods are being sought to improve the measurement of bulkiness in food powders. This study aimed to design a new measuring device to assess the phenomenon of caking as well as the degree of strength of free-flowing powders. Wheat flour and potato starch have been used in the experiment and loaded into a perforated container. A steel or polypropylene measuring rod has been placed in the middle, and 5 kPa and 10 kPa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The more intensive water absorption by starch particles at higher ambient humidity resulted in an extended sliding time of starch particles in con-tact. Wajs et al [20] did not observe such a trend for potato starch with a moisture content of 9.5%. These authors reported that, regardless of the consolidation load, the number of oscillations was 40 and 30 for the rod made of steel and polypropylene, respectively.…”
Section: Slip-stick Effectmentioning
confidence: 86%
See 3 more Smart Citations
“…The more intensive water absorption by starch particles at higher ambient humidity resulted in an extended sliding time of starch particles in con-tact. Wajs et al [20] did not observe such a trend for potato starch with a moisture content of 9.5%. These authors reported that, regardless of the consolidation load, the number of oscillations was 40 and 30 for the rod made of steel and polypropylene, respectively.…”
Section: Slip-stick Effectmentioning
confidence: 86%
“…Measurements were conducted using a pull-based tester specifically designed for assessing the strength of consolidated bulk materials. A detailed description of the tester with figures and measurement methods is presented in detail in the work [20] and patents PAT.241621 and PAT.241622. The pull-based tester consisted of a perforated cylindrical vessel with dimensions of 24 mm in diameter and 30 mm in height, featuring a mesh diameter of 1.5 mm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations